Español en SPOC: the search for a solution for teaching Spanish for ENEM in the midst of a pandemic - Fontana, Marcus Vinícius Liessem (2022)
In this work, based on the principles of the connectivist theory of Siemens (2004; 2007) and Downes (2016), identified as a learning theory for the digital age, we present, within the framework of CALL (Computer Assisted Language Learning), the proposal of a SPOC (Small Private Online Course) aimed at teaching Spanish for ENEM. The course, entirely online and in a gamified model, was developed in the MOODLE virtual environment, based on the DBR (Design Based Research) methodology. DBR entails needs analysis, development and application of an educational resource for subsequent evaluation and redesign. Here, in addition to presenting the course originally developed, we report two failed application attempts with two different high school classes during the most difficult moments of the COVID-19 pandemic. We also bring our considerations about the possible causes of failure. At the moment, we try to adapt the course to apply it in the flipped classroom modality, which is a hybrid modality, in order to verify one of our hypotheses, that the difficulties encountered were due to the fact that the course was exclusively distance learning.